2023
DOI: 10.1111/jvim.16657
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiome in dogs with lymphoid and nonlymphoid tumors

Abstract: Background The association of gut microbiota with cancer etiology and prognosis has been demonstrated in humans and rodents but has not been studied in dogs with different types of tumors. Hypothesis/Objectives To analyze microbiome composition according to tumor progression based on metastasis, recurrence, and therapeutic response in canine tumors. Animals Thirty‐two client‐owned dogs were divided into 3 groups: healthy (n = 9), with lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…This was evident in the distinct clustering of the two groups in the PCoA plots based on Bray-Curtis and Jaccard distances, as well as the differential abundance analysis at the genera level. The phyla Actinobacteria, Bacteroidetes, Firmicutes, Fusobacteria, and Proteobacteria were detected in both groups, aligning with prior research on the gut microbiome of canines [16,19,35]. We observed that the family Clostridiaceae was overexpressed, consistent with previous studies on insulin-dependent diabetic dogs [36,37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was evident in the distinct clustering of the two groups in the PCoA plots based on Bray-Curtis and Jaccard distances, as well as the differential abundance analysis at the genera level. The phyla Actinobacteria, Bacteroidetes, Firmicutes, Fusobacteria, and Proteobacteria were detected in both groups, aligning with prior research on the gut microbiome of canines [16,19,35]. We observed that the family Clostridiaceae was overexpressed, consistent with previous studies on insulin-dependent diabetic dogs [36,37].…”
Section: Discussionsupporting
confidence: 91%
“…Knowing the diversity and taxonomic bacterial distribution of the gut microbiota may provide hints regarding the onset and progression of corresponding diseases. Accumulating evidence suggests that various diseases, including cancers and cardiovascular diseases, affect canine gut microbial composition [16][17][18][19]. Yet, no such research has been conducted regarding canine diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%